EFFECT OF GANDHAKA KALPA INTERNALLY AND KSHEERABALA 101 AVARTI TAILA NASYA IN DRY AGE RELATED MACULAR DEGENERATION- A CLINICAL STUDY - Nair, Aiswarya.V.; Salam, A.Abdul; K, Ambili (International Journal of Ayurveda and Pharma Research, 2019)
Introduction: Age-related macular degeneration (AMD) is a neurodegenerative disease which is one of the leading causes of vision loss affecting population above the age of 50 years. Of the two types wet and dry AMD, dry AMD constitute 90% of cases. Currently there is no effective treatment for AMD except for antioxidant supplementation which can delay the progression of AMD and its associated vision loss. In Ayurveda, it is a Vata Pitthadhika Drishtigata Roga compounded by Dhatukshaya in Vardhakya. The treatment should be Brimhana, Chakshushya and Rasayana to tackle the degenerative changes. Gandhaka Kalpa from Rasaratnasamucchaya and Ksheerabala 101 Avarti Taila has these properties to ameliorate the disease pathology. Hence a clinical study was planned with the objective to assess the effect of Gandhakakalpa internally and Ksheerabala 101 Avarti Taila Nasya in dry AMD.Methods: The study design was interventional, pre and post evaluation without control. After preparatory phase, patients were given Nasya with Ksheerabala 101 Avarti Taila followed by administration of Gandhaka Kalpa with concurrent administration of Ksheerabala 101 Avarti Taila as Pratimarsa Nasya. Study and follow up were done in 30 eyes. Results were documented and statistically analysed using Friedmains’s test, paired t test, Wilcoxon’s signed rank test and McNemar test according to type of variable.Result: The intervention is statistically significant while considering visual acuity (p < 0.001) and Daily Living Tasks Dependent on Vision questionnaire scores (p< 0.0001) and not significant for optical coherence tomography and Amsler grid findings.Conclusion: The intervention is an effective protocol to be followed in Ayurveda for dry AMD.